Seed-Soaking with Melatonin for the Improvement of Seed Germination, Seedling Growth, and the Antioxidant Defense System under Flooding Stress - Hongli Zeng; Minghao Liu; Xin Wang; Ling Liu; Huiyi Wu; Xuan Chen; Haodong Wang; Quansheng Shen; Guanghui Chen; Yue Wang (Agronomy, 2022)
Flooding is the main cause of inhibited seed germination and seedling growth during the direct seeding of rice. As a growth-regulating hormone, melatonin plays an important role in promoting seed germination and enhancing plant stress resistance. However, there are still many unknown mechanisms related to the exogenous-melatonin-mediated regulation of submergence tolerance during seed germination. To overcome these challenges, this study investigated the effects of seed-soaking with different melatonin concentrations on the germination and physiological characteristics of rice seeds over different flooding times. The results showed that the exogenous administration of 100 μM of melatonin significantly improved the germination potential, germination rate, germination index, and vigor index of seeds and increased the size of the aboveground and underground biomass. By increasing the activities of superoxide dismutase (SOD) and peroxidase (POD) in shoots and roots, and reducing the content of malondialdehyde (MDA), the 100 μM melatonin alleviated the damage of rice seeds under flooding stress. The gray relational grade between the root MDA content and the melatonin seed-soaking treatment was the highest, and this was used to evaluate the effect of melatonin in alleviating flooding stress. A two-factor analysis of variance showed that the flooding stress treatment and the melatonin treatment had more significant effects on rice seed germination than the flooding and melatonin interaction treatments (p < 0.01). The optimal number of days for rice seeds to resist flooding stress was two, and the optimal concentration for the melatonin seed-soaking treatment was 100 μM. In sum, a 100 μM melatonin seed-soaking treatment can effectively alleviate the damage of flooding stress on rice seeds and promote the growth and development of seedlings. This study provides the theoretical basis for a light and simple cultivation technique for the direct seeding of rice.